2013
DOI: 10.1155/2013/245804
|View full text |Cite
|
Sign up to set email alerts
|

IRF5 Is a Specific Marker of Inflammatory MacrophagesIn Vivo

Abstract: Macrophages are an integral part of the innate immune system and key players in pathogen clearance and tissue remodelling. Both functions are accomplished by a pivotal network of different macrophage subtypes, including proinflammatory M1 and anti-inflammatory M2 macrophages. Previously, our laboratory identified the transcription factor interferon regulatory factor 5 (IRF5) as the master regulator of the M1 macrophage polarisation. IRF5 was found to be highly expressed in human M1 compared to M2 macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 41 publications
(50 reference statements)
11
87
0
1
Order By: Relevance
“…Here, we used human GM‐CSF and M‐CSF to polarize rabbit macrophages from peripheral blood monocytes, because there are no commercially available rabbit recombinant proteins for polarization of rabbit macrophages. When applied to murine macrophages, recombinant human M‐CSF induces the M2 phenotype, but human GM‐CSF does not induce the M1 phenotype in mice 21. Human M‐CSF and GM‐CSF share 83% and 69% amino acid identity with corresponding regions of rabbit M‐CSF and GM‐CSF, and 81% and 55% with mouse, respectively (data from National Center for Biotechnology Information; http://www.ncbi.nlm.nih.gov/).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used human GM‐CSF and M‐CSF to polarize rabbit macrophages from peripheral blood monocytes, because there are no commercially available rabbit recombinant proteins for polarization of rabbit macrophages. When applied to murine macrophages, recombinant human M‐CSF induces the M2 phenotype, but human GM‐CSF does not induce the M1 phenotype in mice 21. Human M‐CSF and GM‐CSF share 83% and 69% amino acid identity with corresponding regions of rabbit M‐CSF and GM‐CSF, and 81% and 55% with mouse, respectively (data from National Center for Biotechnology Information; http://www.ncbi.nlm.nih.gov/).…”
Section: Discussionmentioning
confidence: 99%
“…This was accomplished by immunohistochemistry, where double stainings were performed for Mac3 (general macrophage marker) in combination with IRF5, YM1, or IL-10 to identify M1-dominant, M2-dominant, and anti-inflammatory macrophages, respectively. IRF5 has been shown to be a specific marker for M1-dominant macrophages in vivo and in vitro (9,27), inducing transcription of genes encoding IL-12 and IL-23 and suppressing the gene encoding IL-10 in diverse disease settings. YM1 is a unique marker for M2-dominant macrophages in the lung (4,23).…”
Section: Discussionmentioning
confidence: 99%
“…The model is characterized by infiltration of polymorphonuclear and mononuclear cells, pannus formation, and erosion of bone and cartilage (17), and is Th17 dependent (18). We have previously reported that synovial macrophages from the AIA-affected joints are characterized by high levels of IRF5 (16). Here, we aimed to determine the role that IRF5 plays in synovial physiology and function in both naïve joints and during inflammatory arthritis.…”
Section: Significancementioning
confidence: 98%
“…We have documented the importance of the transcription factor IFN regulatory factor 5 (IRF5) in defining the classical inflammatory phenotype of macrophages (15,16). IRF5 has also recently been reported to be expressed in neutrophils, specifically in neutrophils from synovial fluid of arthritic mice (13).…”
mentioning
confidence: 99%